Exploring the Dynamics of Recruitment Deception in Global Labor Exploitation: From Policy to Practice - Eka Wahyu Kasih; Benardi Benardi; Grace Yulianti (LPPM STIE Kasih Bangsa, 2024)
This qualitative literature review investigates the phenomenon of recruitment deception within the framework of global labor exploitation. It explores the disconnect between existing policies designed to protect workers and the actual practices in recruitment processes across various industries and geographical regions. By analyzing a range of scholarly articles, reports, and case studies, the review identifies prevalent deceptive practices that exploit vulnerable populations, including migrant workers and those in precarious employment situations. The findings reveal significant gaps in the enforcement of protective legislation and highlight the emotional and psychological impacts of deception on affected individuals. Furthermore, the review emphasizes the necessity for collaborative efforts among stakeholders—including governments, non-governmental organizations, and community groups—to create effective interventions that address these injustices. Ultimately, the study calls for a more inclusive policy-making process that incorporates the experiences of survivors, aiming to develop comprehensive strategies to combat recruitment deception and enhance labor market equity.